2020
DOI: 10.1111/apm.13035
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic features and prognostic factors in patients with renal cell carcinoma with sarcomatoid differentiation

Abstract: Clinicopathologic features and prognostic factors in patients with renal cell carcinoma with sarcomatoid differentiation. APMIS 2020; 128: 378-386.Renal cell carcinoma with sarcomatoid differentiation (RCCs) is rare, accounting for 1-8% of all RCC histological subtypes. In this study, we examined 139 patients with RCCs and aimed to explore their clinicopathologic features and prognostic factors. From January 2007 to January 2019, patients who were pathologically diagnosed with RCCs were included in this retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…With the approximate 270,000 new cases worldwide per year, renal cell carcinoma (RCC) represents 2 to 3% of all adult malignant tumors and ascends to the most common genitourinary cancer [1]. Based on the various molecular genetic features, RCC was identified as different histopathologic classifications, of which clear cell renal cell carcinoma (ccRCC) comprised the main histopathologic subtype, accounting for 70 to 80% of RCC [2].…”
Section: Introductionmentioning
confidence: 99%
“…With the approximate 270,000 new cases worldwide per year, renal cell carcinoma (RCC) represents 2 to 3% of all adult malignant tumors and ascends to the most common genitourinary cancer [1]. Based on the various molecular genetic features, RCC was identified as different histopathologic classifications, of which clear cell renal cell carcinoma (ccRCC) comprised the main histopathologic subtype, accounting for 70 to 80% of RCC [2].…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al examined 139 RCC patients and aimed to explore the relationship between clinical and pathologic features with prognostic factors and indicated that microvascular invasion was a significant predictor of prognosis (24). Bernardos et al retrospectively analyzed 153 pT3apN0cM0 kidney cancer patients and indicated that tumor necrosis and microvascular invasion were associated with tumor recurrence (25).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that patients with sarcomatoid carcinoma have a poorer prognosis than classical ccRCC [8,26], therefore uncovering the genomic characterization of sarcomatoid transformation in ccRCC is vital. The most altered pathways of sarcomatoid RCC (sRCC) involved VHL (72%), chromatin remodeling genes (72%), MTOR pathway (50%), DNA repair (30%), and the Hippo-YAP pathway (20%) [27].…”
Section: Discussionmentioning
confidence: 99%